Public procurement and innovation - Caranta, Roberto (2021)
Innovation has come to the forefront of EU public procurement. Directive 2014/24/EU has given contracting authorities in the Member States a new award procedure to pursue innovation, namely the innovation partnership. Still a number of issues remain open, notably concerning the allocation of intellectual property rights that may call for the application of State aids rules. Further guidance is thus expected from the Commission.